Contrast visual acuity in patients with retinitis pigmentosa assessed by a contrast sensitivity tester - Oishi, Maho (Medknow Publications & Media Pvt Ltd, 2012)
PURPOSE: To assess contrast visual acuity (CVA) in patients with retinitis pigmentosa (RP) and compare the result with standard visual acuity (VA), retinal thickness, status of inner segment/outer segment junction, and central visual field. MATERIALS AND METHODS: Thirty-nine eyes of 39 patients with RP and 39 eyes of 39 healthy individuals were studied. To see the difference in CVA between RP patients and normal controls, only subjects with standard VA of 1.0 (20/20) or better were included. This was a cross-sectional study. CVA in various light conditions was measured with CAT-2000 and was compared between patients and controls. CVA of patients was further analyzed for association with other parameters including foveal retinal thickness, outer nuclear layer thickness, the status of inner segment/outer segment junction measured with optical coherence tomography (OCT), and visual field mean deviation (MD) measured with Humphrey field analyzer 10-2 program. RESULTS: CVA impairment was evident in RP patients compared to controls (P < 0.01, in all measurement conditions). Multivariate analysis showed association of logarithm of the minimum angle of resolution (logMAR) with CVAs in several conditions. None of the OCT measurements was associated with CVA. When patients were divided into three groups based on MD, the most advanced group (MD worse than or equal to –20 dB) showed impairment of mesopic CVA (P < 0.05, under mesopic condition of 100% without glare, with glare, and 25% without glare). CONCLUSION: CVA impairment was confirmed in RP patients, especially in advanced cases. CVA measured with CAT-2000 may be a useful tool for assessing foveal function in RP patients.